Characterization of the binding mode of the PET tracer [18F]ASEM to a chimera structure of the α7 nicotinic acetylcholine receptor. Issue 32 (4th April 2017) - Kuang, Guanglin; Zhou, Yang; Zou, Rongfeng; Halldin, Christer; Nordberg, Agneta; Långström, Bengt; Ågren, Hans; Tu, Yaoquan
Abstract : The binding free energy profile of the radio-ligand [ 18 F]ASEM with the α7 nicotinic acetylcholine receptor was revealed by metadynamic simulations. Abstract : The α7 nicotinic acetylcholine receptor (α7-nAChR) is assumed to be implicated in a variety of neurological disorders, such as schizophrenia and Alzheimer's disease (AD). The progress of these disorders can be studied through imaging α7-nAChR with positron emission tomography (PET). [ 18 F]ASEM is a novel and potent α7-nAChR PET radioligand showing great promise in recent tests. However, the mechanism of the molecular interaction between [ 18 F]ASEM and α7-nAChR is still unclear. In this paper, the binding profile of [ 18 F]ASEM to a chimera structure of α7-nAChR was investigated with molecular docking, molecular dynamics, and metadynamics simulation methods. We found that [ 18 F]ASEM binds at the same site as the crystallized agonist epibatidine but with a different binding mode. The dibenzo[ b, d ]thiophene ring has a different orientation compared to the pyridine ring of epibatidine and has van der Waals interactions with residues from loop C on one side and π–π stacking interaction with Trp53 on the other side. The conformation of Trp53 was found to have a great impact on the binding of [ 18 F]ASEM. Six binding modes in terms of the side chain dihedral angles χ 1 and χ 2 of Trp53 were discovered by metadynamics simulation. In the most stable binding mode, Trp53 adopts a different conformation from that in the crystalline structure and has a rather favorable π–π stacking interaction with [ 18 F]ASEM. We believe that these discoveries can be valuable for the development of novel PET radioligands.